Synthesis of porous pig bone char as adsorbent for removal of DBP precursors from surface water - Aunnop Wongrueng (2019)
© IWA Publishing 2019 Water Science & Technology This research study aims to investigate the efficiency of synthesized porous pig bone char (PBC) for reduction of disinfection by-product (DBP) precursors from surface water. Dissolved organic matter (DOM) is commonly present in natural water and acts as a disinfection by-product precursor. Adsorption is one of the promising technologies that is commonly applied for DOM removal. Interestingly, the properties of pig bone are such that it has a surface area and pore volumes that can adsorb DOM. Pig bone was synthesized as porous bone char (PBC). The results show that synthesized PBC at 900 C (PBC-900 C) provides a high volume of mesoporous structure. The adsorption process was best fitted with the pseudo-second-order and Freundlich isotherm model. Thus, the mechanisms occurred on the multilayer adsorption of the surface. PBC-900 C can remove approximately 70-80% of DOM with varying concentrations, from 0.2 g/L to 0.8 g/L. Furthermore, the results of fluorescence excitation-emission (FEEM) showed that humic acids and humic-like substances in water can be removed by using PBC at concentrations higher than 0.4 g/L. From the obtained results, it can be concluded that PBC is an alternative low-cost adsorbent which can be utilized for reduction of DBP precursors from water.